Exploiting Asynchrony in Multi-agent Con-sensus to Change the Agreement Point - Pellitero, Diego; Sánchez, David; Hernández, Mario; Serrano, Álvaro (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2018)
Reaching agreement by consensus is fundamental to the operation of distributed systems, such as sensor networks, social networks or multi-robot networks. In real systems, the resource limitations available to individual agents and communication delays typically result in asynchronous control models of discreet time for consensus. In this paper, we model the problem where a set of agents arrive at a consensus on the value of a variable of interest, being guided by one of them.